Hydrodynamic Study on the Internal Design of a Micromixer under laminar condition using Computational Fluids Dynamics (CFD) - Shukhairie bin Salim, Shukhairie (Universiti Teknologi Petronas, 2011)
This project has a purpose to give contribution in the micro-engineering field; the development of efficient micromixers designs has become a focus research by the industry. Mixing is a critical process because the quality of the final product and its attributes are derived by the quality of the mix. Improper mixing results in a non-homogenous product that lacks consistency with respect to desired attributes like chemical composition, color, texture, flavor, reactivity, and particle size. The wide variety and ever increasing complexity of micro-mixing processes encountered in industrial applications requires careful selection, design, and scale up to ensure effective and efficient mixing. Today, with the advancement of technology, mixing problem scan be investigated by using computational fluid dynamics (CFD). CFD simulation helps researchers to predict and understand the mixing behavior in each micromixer designs in more economical way. Micromixer designs are constructed based on trial and errors with creative combination from common industrial micromixer. Each design is evaluated according to criteria assigned. The best three (3) micromixer will be selected for further post processing and modification. Study also been conducted to study the impact of scale up & scale down the micromixer to meet the industrial requirement for testing and experiments in the lab. Micromixer is no longer a generic production tool, but a critical and decisive business tool. This is because profitability and competitive advantage are depending upon subtle improvements in product quality through gains in mixing performance and efficiency.